Mapping technology-harm relations: from ambient harms to zemiosis - Wood, Mark A. (Crime, media, culture, 2022)
This article develops a new approach to analysing the technology-harm nexus. The approach distinguishes between different technology-harm relations: relations with technology that are harmful by virtue of what they contribute to bringing about. In this article, I focus on categorizing generative harm relations: relations with technology that are harmful by virtue of what they do to actors. Drawing together insights from zemiology, moral philosophy, postphenomenology, Stiegler?s technophenomenology, and Latour?s actor-network theory, I distinguish six generative harm relations: ambient harms, alterity harms, exclusion harms, interface harms, harm translation and zemiosis. Distinguishing between these generative harm relations helps us delineate the techno-sociality of a range of social harms, from gun violence and digital coercive control, to forms of oppression, inequality and immiseration (re)produced by algorithms.